Voltage regulation and minimization of loses in the presence of renewable energy sources on the medium voltage network - Dib, M.; Nejmi, A.; Ramzi, M.; Elhafyani, M. (International Journal of Engineering and Technology, 2020)
The Moroccan electricity network has been designed and sized to work with high power outputs connected to the transmission network. This it delivers a unidirectional power flow from production to consumption. In this configuration, the electricity network carries electricity from production plants mainly connected to the transmission network to customers through the distribution network. Therefore, voltage-setting devices on the distribution network such as load-adjustable power transformers and medium voltage MV capacitor banks are set and operated. The inclusion of the Decentralized Generation (DG) based on renewable energies can induce a reversal of the power flow on the distribution network. This raises problems of voltage regulation in the presence of renewable energy sources. This article shows the limit of the current voltage regulation deployed solutions and exposes a solution for adjusting the voltage on the distribution grid in the presence of renewable energy sources connected to medium voltage MV. We will apply ETAP software to a real network located in the eastern zone for the conducted investigation. Later, an optimization approach aiming to minimize losses and improve the voltage plan will be presented at the end.Â Â